2013
DOI: 10.7243/2049-9752-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of C-MAC videolaryngoscopy for direct and indirect assisted endotracheal intubation

Abstract: Background: The experiences of seasoned practitioners with the new C-MAC indirect videolaryngoscope system have shown promising results in the management of difficult airways. However, a comparison of direct and indirect laryngoscopy utilizing the C-MAC system as its own control has not been performed in a cohort of anesthesiologists-in-training. The primary aim was to compare direct and indirect laryngoscopy in terms of intubation time with secondary outcomes including laryngoscopy time and airway view with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
2
0
2
Order By: Relevance
“…Further studies with larger sample size are required to validate the findings of the study. No significant difference in the total intubation time between the C-MAC and the Macintosh laryngoscope group was noted in our study which is in accordance with the findings of Cattano et al [12]. On the contrary, the time to intubate was significantly shorter in Group V as compared to Group M (24 s vs. 68 s) in study by Rajan et al [10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Further studies with larger sample size are required to validate the findings of the study. No significant difference in the total intubation time between the C-MAC and the Macintosh laryngoscope group was noted in our study which is in accordance with the findings of Cattano et al [12]. On the contrary, the time to intubate was significantly shorter in Group V as compared to Group M (24 s vs. 68 s) in study by Rajan et al [10 ].…”
Section: Discussionsupporting
confidence: 91%
“…[24] According to Lee JH et al, 0 the increased number of attempts during tracheal intubation was found to be associated with increased risk of desaturations and tracheal intubation associated events (TIAEs) Our study was inconsistent with that of the Cattano et al, where no significant difference in the total intubation time was observed among the C-MAC and the Macintosh laryngoscope group. [25,26] studies by Shin et al, Kinicaslan et al,similar observations were obtained where the C-MAC was found to be associated with an improved laryngeal view as well as with a higher success rate of intubation compared to the Macintosh blade. [27,28] The percentage of glottis view among the patients intubated using the C-MAC video laryngoscope was found to be 80.67% whereas with conventional Macintosh laryngoscope it was found to be 61.33%.…”
Section: Resultsmentioning
confidence: 53%
“…Pada penelitian lain pun didapatkan hasil waktu intubasi yang sedikit lebih lama pada kelompok dengan metode videolaringoskopi dibanding dengan metode laringoskopi direk. 4, 28,29 Pada penelitian ini didapatkan manuver eksternal laring lebih sedikit dilakukan pada kelompok VL dibanding dengan kelompok direk.…”
Section: Subjek Dan Metodeunclassified
“…16 Hasil ini sesuai dengan hasil penelitian-penelitian sebelumnya. 4, 28,29 Metode videolaringoskopi juga memiliki kelebihan lain, yaitu videolaringoskop secara signifikan meningkatkan jarak mulut ke mulut antara operator dan subjek serta menempatkan wajah operator di atas garis lurus aksis oral-faring-laring sehingga mengurangi risiko penularan mikrob akibat tindakan aerosol. 30 Penggunakan metode videolaringoskopi juga memiliki kelebihan dapat digunakan sebagai konfirmasi insersi ETT oleh personil lain di samping operator karena memiliki akses visualisasi melalui layar kamera.…”
Section: Subjek Dan Metodeunclassified